Urine and fecal microbiota in a canine model of bladder cancer and comparison of canine and human urine microbiota. Issue 1 (31st December 2022) - Mrofchak, Ryan; Madden, Christopher; Evans, Morgan V.; Kisseberth, William C.; Dhawan, Deepika; Knapp, Deborah W.; Hale, Vanessa L.
Abstract : Urothelial carcinoma (UC) is the tenth most diagnosed cancer in humans worldwide. Dogs are a robust model for invasive UC as tumor development and progression is similar in humans and dogs. Recent studies in humans have revealed alterations in urine microbiota in individuals with UC; however, microbial alterations in dogs with UC have not been evaluated. The objective of this pilot study was to compare the urine and fecal microbiota of dogs with UC and matched healthy controls. DNA was extracted from urine and fecal samples followed by 16S rRNA sequencing and analyses using QIIME2 and R. Dogs with UC had significantly decreased microbial diversity (Kruskal–Wallis; Shannon, p  = 0.048) and altered microbial composition (PERMANOVA: Unweighted UniFrac, p  = 0.011) in urine, but not fecal samples. The relative abundance of Fusobacterium was also increased, although not significantly, in urine and fecal samples of dogs with UC. A comparison of canine and human urine microbiota further revealed similarities in dominant microbial taxa across both host species. This study supports the value of dogs as a model for studies on bladder cancer and urine microbiota, and it provides a foundation for future work exploring host-microbe dynamics in UC carcinogenesis, prognosis, and treatment.